2015
DOI: 10.1021/acs.orglett.5b00840
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Diazo Scaffold for Protein Esterification

Abstract: The O-alkylation of carboxylic acids with diazo compounds provides a means to esterify carboxylic acids in aqueous solution. A Hammett analysis of the reactivity of diazo compounds derived from phenylglycinamide revealed that the p-methylphenylglycinamide scaffold has an especially high reaction rate and ester:alcohol product ratio, and esterifies protein carboxyl groups more efficiently than does any known reagent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
73
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 33 publications
0
73
0
6
Order By: Relevance
“…Maintaining chemoselectivity in the presence of water and other biological nucleophiles has been a primary challenge in developing diazo compounds as useful tools for protein chemistry. 128,129 …”
Section: Protein Alkylationmentioning
confidence: 99%
See 2 more Smart Citations
“…Maintaining chemoselectivity in the presence of water and other biological nucleophiles has been a primary challenge in developing diazo compounds as useful tools for protein chemistry. 128,129 …”
Section: Protein Alkylationmentioning
confidence: 99%
“…129 A Hammett analysis of these compounds, which were derived from phenylglycine, revealed that electron-donating or electron-withdrawing groups on the aryl ring had a dramatic effect on the rate of esterification. Still, the compounds were similar in their selectivity for ester formation over hydrolysis of the diazo reagent.…”
Section: Bioreversible Protein Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Recently, we found that appropriately tuned diazo compounds can esterify protein carboxyl groups, providing a second type of bioreversible modification. 44,45 In this work, we report on a bioreversible modification of protein amino groups that is distinct from others 4648 in its reliance on enzymatic catalysis. With its traceless utility in promoting cellular uptake, B-TML–NHS ester provides new opportunities in chemical biology and pharmacology.…”
mentioning
confidence: 98%
“…Notably, the full mass of the diazo compound had been added to the peptide, ruling out the possibility of reaction by esterification, as is possible with diazo groups. 10 …”
mentioning
confidence: 99%